Maharashtra State BoardSSC (English Medium) 7th Standard

Simplify the Expression. 140 ÷ (( – 11) × ( – 3) – ( – 42) ÷ 14 – 1) - Mathematics

Advertisements
Advertisements
Sum

Simplify the expression.

140 ÷ [( – 11) × ( – 3) – ( – 42) ÷ 14 – 1]

Advertisements

Solution

140 ÷ [( – 11) × ( – 3) – ( – 42) ÷ 14 – 1]

= 140 ÷ [33 – ( – 42) ÷ 14 – 1]

= 140 ÷ [33 + 42 ÷ 14 – 1]

= 140 ÷ [33 + 3 – 1]

= 140 ÷ [36 – 1]

= 140 ÷ 35

= 4

  Is there an error in this question or solution?
Chapter 5: Operations on Rational Numbers - Practice Set 25 [Page 42]

APPEARS IN

Balbharati Mathematics 7th Standard Maharashtra State Board
Chapter 5 Operations on Rational Numbers
Practice Set 25 | Q 3 | Page 42
Share
Notifications



      Forgot password?
Use app×